'Enough to Keep Them Alive': Indian Welfare in Canada, 1873-1965 - Finkel, Alvin (Labour / Le Travail, 2005)
The article reviews the book, "'Enough to Keep Them Alive':Indian Welfare in Canada, 1873-1965," by Hugh Shewell.